2010
DOI: 10.1074/jbc.m109.016741
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl Pyrophosphate Inhibits Epithelialization and Wound Healing through the Glucocorticoid Receptor

Abstract: Farnesyl pyrophosphate (FPP), a key intermediate in the mevalonate pathway and protein farnesylation, can act as an agonist for several nuclear hormone receptors. Here we show a novel mechanism by which FPP inhibits wound healing acting as an agonist for glucocorticoid receptor (GR). Elevation of endogenous FPP by the squalene synthetase inhibitor zaragozic acid A (ZGA) or addition of FPP to the cell culture medium results in activation and nuclear translocation of the GR, a known wound healing inhibitor. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 39 publications
3
88
0
2
Order By: Relevance
“…This effect was due to the blockade of FPP's activation of the GR. 9 Taken together, this finding establishes a second, upstream mechanism whereby the stress hormone pathway can be activated in epidermis. The role of FPP in the pathogenesis of chronic wounds and their nonmigratory keratinocytes needs further investigation.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 85%
See 4 more Smart Citations
“…This effect was due to the blockade of FPP's activation of the GR. 9 Taken together, this finding establishes a second, upstream mechanism whereby the stress hormone pathway can be activated in epidermis. The role of FPP in the pathogenesis of chronic wounds and their nonmigratory keratinocytes needs further investigation.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 85%
“…9 However, studies have shown that enhanced keratinocyte migratory potential is not mediated through the inhibition of cholesterol synthesis despite the disrupted skin barrier. This effect was due to the blockade of FPP's activation of the GR.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
See 3 more Smart Citations